Assessment of facial aesthetics based on photography – first impression and aesthetic lines. Part I (Journal of Face Aesthetics, 2025)
Introduction. The perception of beauty depends on many factors. The evaluation of aesthetics by doctors, such as orthodontists and maxillofacial surgeons, focuses on anatomical and functional aspects, while random evaluators base their assessments on intuitive preferences. Facial profile assessments use lines like Ricketts, Barcelona and TVL, among others, but the subjectivity of beauty perception makes these assessments require an understanding of patients' expectations. Aim. The purpose of this study was to evaluate the first impression of the face in frontal and profile.Material and methods. 180 black‑and‑white photographs of faces were used. The photographs were of subjects of different ages of both sexes. A VAS scale from 0 to 10 was used for evaluation, with 0 being the lowest rating and 10 being the highest rating. The photographs were rated by three groups of people: random evaluators (laypeople), dentists and doctors of various medical specialties.Results. Doctors gave significantly lower ratings for both en face and profile compared to random evaluators (laypeople). Among dentists, the ratings given were also lower relative to random evaluators (laypeople), but without statistical significance.Conclusions. An attractive profile is often related to social preferences, not just anatomical norms. This means that evaluating a facial profile requires not only accurate measurements, but also an understanding of patients' aesthetic expectations.
Keywords: facial profile; first impression; Barcelona line; Ricketts line; TVL